2013
DOI: 10.7567/jjap.52.08je13
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of GaN Nanowall Network and Optical Property of InGaN/GaN Quantum Wells by Molecular Beam Epitaxy

Abstract: A GaN nanowall network and InGaN/GaN quantum wells were grown on AlN/Si(111) substrates by molecular beam epitaxy (MBE). The morphology, polarity, structural, and optical properties of the GaN nanowall network were investigated. The lattice constants a 0= 3.193 Å and c 0 = 5.182 Å of the GaN nanowall network were obtained by X-ray diffraction (XRD), indicating that the GaN nanowall network is under low stress. Chemical etching test shows that the GaN nanowall network grown o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 27 publications
(27 reference statements)
2
19
0
Order By: Relevance
“…[18][19][20][21][22] The N to Ga ratio also determines the width of the nanowalls as reported previously.…”
Section: Structural Properties Of Lmbe Grown Homoepitaxial Gan Nanostsupporting
confidence: 53%
See 3 more Smart Citations
“…[18][19][20][21][22] The N to Ga ratio also determines the width of the nanowalls as reported previously.…”
Section: Structural Properties Of Lmbe Grown Homoepitaxial Gan Nanostsupporting
confidence: 53%
“…Recently, a few research groups have reported the growth of GaN nanowall networks on sapphire 18,21 and Si(111) 19,20 using plasma assisted molecular beam epitaxy (PA-MBE). Most of the GaN nanowall networks have been grown heteroepitaxially on these substrates under extremely high N to Ga ux ratio conditions.…”
Section: 18-22mentioning
confidence: 99%
See 2 more Smart Citations
“…Most of the growth of porous GaN is achieved by top down approaches such as chemical etching 19 or ion bombardment 20 , which limit the device performance due to contamination, undesired interface and defect states, and degradation in crystallinity and composition. Previously, we have shown that by controlling V/III ratio, spontaneous formation of porous nanostructures can be achieved by using PA-MBE system, 21-24 which was followed by a few groups [25][26][27][28] . Investigations of the growth process of NwN are highly important to control shape and size of the pores, to enhance light extraction efficiency 22 .…”
Section: Introductionmentioning
confidence: 99%